![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
d) |2x – 5| –7 = 22
| 2x -5 | = 22+7
| 2x -5 | = 29
TH1: 2x-5 = -29
2x = -29+5
2x= -24
x= -24:2
x= -12
TH2: 2x -5 =29
2x = 29+5
2x= 34
x= 34:2
x= 17
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
a,\(\left(x-15\right):50+22=24\)
\(< =>\frac{\left(x-15\right)}{50}=2< =>x-15=100\)
\(< =>x=100+15=115\)
b,\(42-\left(2x+32\right)+12:2=6\)
\(< =>42-2x-32=0\)
\(< =>10-2x=0< =>x=\frac{10}{2}=5\)
Làm nốt :
c) \(134-2\left\{156-6\cdot\left[54-2\cdot\left(9+6\right)\right]\right\}\cdot x=86\)
=> 134 - 2{156 - 6 . [54 - 2 . 15]} . x = 86
=> 134 - 2{156 - 6 . [54 - 30]} . x = 86
=> 134 - 2{156 - 6. 24} . x = 86
=> 134 - 2{156 - 144} . x = 86
=> 134 - 2.12 . x = 86
=> 134 - 24 . x = 86
=> 24.x = 48
=> x = 2
Bài 2 : a) 120 : [21 - (4x - 4)] = 23.3
=> 120 : [21 - (4x - 4)] = 8.3
=> 120 : [21 - (4x - 4)] = 24
=> 21 - (4x - 4) = 5
=> 4x - 4 = 16
=> 4x = 20
=> x = 5
b) 3.[205 - (x - 9)] - 486 = 0
=> 3.[205 - (x - 9)] = 486
=> 205 - (x - 9) = 162
=> x - 9 = 205 - 162 = 43
=> x = 43 + 9 = 52
c) 204 - 2{200 - 5.[64 - 2.(11 + 6)]} . x = 4
=> 204 - 2{200 - 5.[64 - 2.17]} . x = 4
=> 204 - 2{200 - 5 .[64 - 34]}.x = 4
=> 204 - 2{200 - 5.30} . x = 4
=> 204 - 2{200 - 150}.x = 4
=> 204 - 2.50 . x = 4
=> 2.50.x = 200
=> 100.x = 200
=> x = 2
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 3(x+3)-2(x-5)=11
=> 3x+9-2x+10=11
=> 3x-2x=11-10-9
=> x=-8
Vậy.........
b, 14-4|x|=-6
=> -4|x|=8
=> |x|=-2(VL vì trị tuyệt đối luôn lớn hơn hoặc = 0)
Vậy......
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:
a)\(x-14=3x+18\)
\(\Rightarrow-14-18=3x-x\)
\(\Rightarrow-32=2x\Rightarrow x=-16\)
b)\(2\left(x-5\right)-3\left(x-4\right)=-6+15.\left(-3\right)\)
\(\Rightarrow2x-10-3x+12=-51\)
\(\Rightarrow-x+2=-51\Rightarrow-x=-51-2=-53\Rightarrow x=53\)
c)\(\left(x+7\right)\left(x-9\right)=0\Rightarrow\left[{}\begin{matrix}x+7=0\\x-9=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=-7\\x=9\end{matrix}\right.\)
d)\(\left|2x-5\right|-7=22\Rightarrow\left|2x-5\right|=22+7=29\)
\(\Rightarrow\left[{}\begin{matrix}2x-5=29\\2x-5=-29\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=17\\x=-12\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, (-72).(15 - 49) + 15.(-56 + 72)
= -72 . 15 + 72.49 - 15.56 + 15.72
= (-72.15 + 15.72) + (72.49 - 15.56)
= 3528 - 84
= 2688
1b, 1532 + (-186) + (-1432) + (-14) + 123
= (1532 - 1432) - (186 + 14) + 123
= 100 - 200 + 123
= 223 - 200
= 23
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1
a) 15-(1+x)=1 b)3+x-(14-22)=-13
1+x =15-1 3+x-(-8)=-13
1+x =14 3+x+8=-13
x = 14-1 3+x=(-13)-8
x=13 3+x=-24
Vậy x=13 x=(-24)-3
x=-27 c)17-(2+x)=3 Vậy x=-27
2+x =17-3
2+x =14
x=14-2
x=12
Vậy x=12